Inhibition and enhancement of contextual fear memory destabilization - Lee, Jonathan L. C.; Flavell, Charlotte R. (Frontiers in Behavioral Neuroscience, 2014)
The reactivation of a memory can result in its destabilization, necessitating a process of memory reconsolidation to maintain its persistence. Here we show that the destabilization of a contextual fear memory is potentiated by the cannabinoid CB1 receptor agonist ACEA. Co-infusion of ACEA and the IKK inhibitor sulfasalazine into the dorsal hippocampus impaired contextual fear memory reconsolidation. This observation was achieved under behavioural conditions that, by themselves, did not result in either a reconsolidation impairment by sulfasalazine alone or reactivation-induced upregulation of Zif268 expression. Moreover, we show that the destabilization of a contextual fear memory is dependent upon neuronal activity in the dorsal hippocampus, but not memory expression per se. The effect on contextual fear memory destabilization of intra-hippocampal ACEA was replicated by systemic injections, allowing an amnestic effect of MK-801. These results indicate that memory expression and destabilization, while being independent from one another, are both dependent upon memory reactivation. Moreover, memory destabilization can be enhanced pharmacologically, which may be of therapeutic potential.